Uji Efektivitas Antibakteri Ekstrak Etanol Bunga Kecombrang (Etlingera elatior) Terhadap Pertumbuhan Klebsiella pneumoniae - Novita Dwi Anggraini; Kartika Manalu Kartika; Efrida Pima Sari Tambunan (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Ginger flower (Etlingera elatior) is an herbal plant that has secondary metabolite compounds that function as antibacterial. Klebsiella pneumoniae bacteria is the cause of penumoniae, urinary tract infections and nosocomial infections. The purpose of this study was to determine the effect of the ethanolic exstract of Etlingera elatior in hibiting the growth of Klebsiella pneumoniae. Work procedure was started extracting ginger flower with 96% ethanol solvent, phythochemical screening test and effectiviness test with Kirby bauwer diffusion method and exstract concentration groups of 10%, 20%, 30%, 40% and 50% as well as positive control of meropenem antibiotics and negative control of distilled water. Data analysis used SPSS 25 with one way ANOVA test and Duncan’s follow-up test. The results showed that the ethanolic exstract of ginger flower was effective in inhibiting the growth of Klebsiella pneumoniae bacteria at concentrations of 30%, 40% and 50%, respectively, with an averange inhibition zone diameter of 14 mm, 15,2 mm and 15,6 mm.